Application of clitoris exposure + episioplasty + dermabrasion + platelet-rich plasma injection + chemexfoliation in vulvar lichen sclerosus - Shang, Xianhui; Chen, Changmei; Ma, Hong; Zhao, Peng; Mao, Yuchen; Liu, Hong; Wang, Cao; Mao, Kaiyi; Luo, Zhen; Li, Yingbo; Zhou, Guangxu; Tan, Hongyang (Frontiers in Pediatrics, 2023)
Objective: To investigate the therapeutic effect of clitoris exposure + episioplasty + dermabrasion + platelet-rich plasma (PRP) injection + chemexfoliation on vulvar lichen sclerosus (VLS). Methods:Twenty children with VLS (under 14 years old) at our hospital from July 2020 to November 2022 were enrolled and treated with clitoris exposure + episioplasty + dermabrasion + PRP injection + chemexfoliation. Additionally, symptomatic changes and improvements in signs were recorded.Results: Significant therapeutic effects were achieved in all children enrolled in this study. The Cattanco score was 8.02 ± 1.22 points before surgery, 2.21 ± 0.70 points 3 months after surgery, and 2.61 ± 0.59 points 6 months after surgery, demonstrating that the score after surgery was significantly lower than that before surgery (p < 0.05). Mild complications (one case of mild vulvar swelling, one case of minor bleeding, and one case of superficial ulcer) were observed in three children after surgery, with an overall complication incidence of 15%; all complications were improved after the intervention, and no severe adverse reactions were observed. Recurrence was observed in one child (5%) 6 months after surgery. Conclusion: Clitoris exposure + episioplasty + dermabrasion + PRP injection + chemexfoliation is an effective approach for the treatment of VLS.